2019
DOI: 10.21273/hortsci13587-18
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhiza Influences Growth and Nutrient Uptake of Asparagus (Asparagus officinalis L.) under Heat Stress

Abstract: Environmental conditions, specifically heat stress, are important factors in asparagus crop production. Arbuscular mycorrhizal fungi (AMF) have been shown to increase plant growth. Effects of heat stress on nutrient uptake have rarely been examined in intact plants, but the limited results indicate that heat stress will decrease uptake; no studies have examined heat stress effects on asparagus nutrient uptake. We examined the effects of AMF, Glomus intraradices, on the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
0
16
1
Order By: Relevance
“…For example, it was reported that treatment with bacteria ( Bacillus amyloliquefaciens or Azospirillum brasilense ) decreased the activity of this enzyme as well as significantly lower expression of the APX1 gene was observed in heat exposed wheat seedlings ( Abd El-Daim et al, 2014 ). A strikingly different finding was reported in several other studies where microbial treatment increased the level of APX accumulation over non-treated plants under high heat conditions ( Maya and Matsubara, 2013 ; Yeasmin et al, 2019 ; Khan et al, 2020b ). The other two enzymes: DHAR and MDHAR, could not be included in our meta-analysis because of the insufficient number of reports, but both of them were found to increase significantly in plants under elevated temperature, and microbial colonization results in lower accumulation as compared to non-colonized plants ( Abd El-Daim et al, 2014 , 2019 ).…”
Section: Meta-analytic Review and Discussion On Plant Tolerance To Th...contrasting
confidence: 87%
See 2 more Smart Citations
“…For example, it was reported that treatment with bacteria ( Bacillus amyloliquefaciens or Azospirillum brasilense ) decreased the activity of this enzyme as well as significantly lower expression of the APX1 gene was observed in heat exposed wheat seedlings ( Abd El-Daim et al, 2014 ). A strikingly different finding was reported in several other studies where microbial treatment increased the level of APX accumulation over non-treated plants under high heat conditions ( Maya and Matsubara, 2013 ; Yeasmin et al, 2019 ; Khan et al, 2020b ). The other two enzymes: DHAR and MDHAR, could not be included in our meta-analysis because of the insufficient number of reports, but both of them were found to increase significantly in plants under elevated temperature, and microbial colonization results in lower accumulation as compared to non-colonized plants ( Abd El-Daim et al, 2014 , 2019 ).…”
Section: Meta-analytic Review and Discussion On Plant Tolerance To Th...contrasting
confidence: 87%
“…Similar results have been reported for Septoglomus deserticola and Septoglomus constrictum (AM fungi) mediated heat stress tolerance in the tomato plant with no apparent changes in SOD activity ( Duc et al, 2018 ). In contrast, a few studies reported a significant increase in SOD in microbial colonized plants under high-temperature stress ( Maya and Matsubara, 2013 ; Yeasmin et al, 2019 ; Bruno et al, 2020 ; Khan et al, 2020a ). Regarding CAT and POD, they showed consistently higher accumulation (CAT, p = 0.021 ; POD, p = 0.006 ) in colonized plants as compared to non-colonized controls under heat stress across various studies ( Figure 6 ).…”
Section: Meta-analytic Review and Discussion On Plant Tolerance To Th...mentioning
confidence: 88%
See 1 more Smart Citation
“…Considering gene loss being a common pattern during the evolution from initial to full mycoheterotrophy, partial mycoheterotrophs may have already lost some genes because of their ability to retrieve carbohydrates from fungi. A. officinalis has been known to be associated with an arbuscular mycorrhizal fungus (AMF), Glomus intraradices , and growing in an environment without the fungus reducing its biomass 37 . Although AMF symbiosis is prevalent in land plants, A. officinalis is among the best-responding plants to AMF association 38 and it can produce a large white spear underground in a few weeks, suggesting that it is worth investigating whether A. officinalis is able to use carbohydrates provided by its associated AMF and whether gene loss in A. officinalis is correlated with its association with AMF.…”
Section: Resultsmentioning
confidence: 99%
“…AMF provides water and nutrients for their host plants with a balance of exudates of photosynthetic products [18]. It has been reported that AMF can enhance various plant tolerance towards abiotic stress such as salinity, temperature stress, drought, heavy metals with several different ways; by increasing antioxidative enzymes' activity at salt stress and high temperature condition [19,20], prevent heavy metals intake by roots [21], and modulating polyamine metabolism in water deficit condition [22].…”
Section: Introductionmentioning
confidence: 99%